Practicality of Web-Based Four-Tier Test to Identify Student's Misconceptions in Chemical Bonding Materials - Yulia Sari; Ratna Kartika Irawati; Helda Rahmawati (JPPS (Jurnal Penelitian Pendidikan Sains), 2023)
Misconceptions can be identified using a four-level test format diagnostic test. However, this test is less effective because it still uses paper/print and requires a long time at the correction stage. Therefore, it is necessary to develop a web-based four-level test. Objective: The purpose of this research is to find out the practicality of a web-based four-level test. Methods: This type of research is descriptive quantitative with data sources from class X MIPA MAN 1 Hulu Sungai Tengah. The data collection technique uses a questionnaire to test practicality. Results: The results of the practicality test obtained an average percentage of 82.5% in the very practical category in aspects of web appearance, image clarity, material suitability, language, paperless, and helping to determine students' abilities and weaknesses in chemical bonding material. Based on this assessment, a web-based four-level practice test product was used to identify misconceptions in class X MIPA MAN 1 Hulu Sungai Tengah. While the results of students' misconceptions on Lewis structure indicators in chemical compounds were 49.21%, ionic bond formation indicators were 39.68%, covalent bond formation indicators were 47.09%, polar covalent compound indicators were 38.89%, metallic bond indicators were 39.42%, and indicators of the physical properties of compounds based on their bonds of 46.03%. All percentages on these indicators include medium criteria. Novelty: Previous researchers have never done this research, which measured students' misconceptions with web-based four-tier tests in chemistry concepts.